Home offices: Plenty of untapped potential - Karl Brenke (DIW Economic Bulletin, 2016)
As far as the share of individuals with a home office is concerned, Germany is below the EU average and lags considerably behind other countries such as France, the UK, or the Scandinavian countries. Only 12 percent of all employees in Germany work primarily or occasionally from home, although this would theoretically be possible in 40 percent of jobs. In most cases, an employee's desire to work from home is not recognized by employers. If these employers were to reconsider their position, however, the share of people working from home could rise to over 30 percent. The disparity between employees wanting to telecommute and the options offered by employers is greatest in the financial sector and in public administration. Well-qualified full-time employees in particular are interested in working from home. The main motive would appear to be more autonomy in managing their own time, not only reconciling work and family life, since there are just as many singles who would like to work from home as there are single parents. Telecommuters often end up working much longer hours than average, and it is not at all uncommon for them to do unpaid overtime. Nevertheless, their job satisfaction is higher than that of other employees- particularly those who would like to work from home but are not given the option.
Keywords: J81; J28; J83; 330; home office work; job satisfaction